Genome-wide identification and expression profiling of two-component system (TCS) genes in Brassica oleracea in response to shade stress - Sadaqat, Muhammad; Umer, Basit; Attia, Kotb A.; Abdelkhalik, Amr F.; Azeem, Farrukh; Javed, Muhammad Rizwan; Fatima, Kinza; Zameer, Roshan; Nadeem, Majid; Tanveer, Muhammad Hammad; Sun, Sangmi; Ercisli, Sezai; et al. (Frontiers in Genetics, 2023)
The Two-component system (TCS) consists of Histidine kinases (HKs), Phosphotransfers (HPs), and response regulator (RR) proteins. It has an important role in signal transduction to respond to a wide variety of abiotic stresses and hence in plant development. Brassica oleracea (cabbage) is a leafy vegetable, which is used for food and medicinal purposes. Although this system was identified in several plants, it had not been identified in B. oleracea yet. This genome-wide study identified 80 BoTCS genes consisting of 21 HKs, 8 HPs, 39 RRs, and 12 PRRs. This classification was done based on conserved domains and motif structure. Phylogenetic relationships of BoTCS genes with Arabidopsis thaliana, Oryza sativa, Glycine max, and Cicer arietinum showed conservation in TCS genes. Gene structure analysis revealed that each subfamily had conserved introns and exons. Both tandem and segmental duplication led to the expansion of this gene family. Almost all of the HPs and RRs were expanded through segmental duplication. Chromosomal analysis showed that BoTCS genes were dispersed across all nine chromosomes. The promoter regions of these genes were found to contain a variety of cis-regulatory elements. The 3D structure prediction of proteins also confirmed the conservation of structure within subfamilies. MicroRNAs (miRNAs) involved in the regulation of BoTCSs were also predicted and their regulatory roles were also evaluated. Moreover, BoTCSs were docked with abscisic acid to evaluate their binding. RNA-seq-based expression analysis and validation by qRT-PCR showed significant variation of expression for BoPHYs, BoERS1.1, BoERS2.1, BoERS2.2, BoRR10.2, and BoRR7.1 suggesting their importance in stress response. These genes showing unique expression can be further used in manipulating the plant’s genome to make the plant more resistant the environmental stresses which will ultimately help in the increase of plant’s yield.More specifically, these genes have altered expression in shade stress which clearly indicates their importance in biological functions. These findings are important for future functional characterization of TCS genes in generating stress-responsive cultivars.